Inhibition of insulin degradation by nonsuppressible insulin-like activity. - Burghen, G (1976)
Nonsuppressible insulin-like activity, provided by three sources, was evaluated for its effect on the proteolytic degradation of insulin utilizing insulin protease obtained from rat liver homogenate as well as liver cell membranes. All three preparations of nonsuppressible insulin-like activity were found to be competitive inhibitors of insulin degradation. In addition human plasma was fractionated yielding an acetone precipitate which was found to have nonsuppressible insulin-like activity and to be a competitive inhibitor of insulin protease.